PENTASHIHAN AL-QUR'AN DIGITAL DI INDONESIA: PERAN, LEGITIMASI DAN OTORITAS LPMQ - Anis Maisya; Nur Rohman (UIN Raden Mas Said Surakarta, 2021)
This article examines the Lajnah Pentashihan Mushaf Al-Qur'an (LPMQ) in Indonesia which has the authority to provide corrections and recommendations, as well to supervise the distribution of Mushaf in Indonesia. In a decade recently, the massive flow of digitalization in Indonesia has also influenced the emergence of variety of digital Qur'ans with various problems. Hence the response and role of LPMQ in digital Qur'an correction process is important. Based on qualitative data and Max Weber's theory of rational-legal authority, this article shows that LPMQ awares and supports the emergence of digital Qur'an in Indonesia with several policies. However, several policies do not seem to work well due to the lack of qualified human resources in the field of Information technology. In this case, LPMQ seems to still maintain the old way in the process of the mushaf ratifying. In terms of authority, LPMQÂ Â has the legitimacy of having the authority to perform ratifying of digital Qur'an. LPMQ as institution also has legality to affirm or certify a product. As well as the authority is allowed to issue an order such as a set of rules, in which it is drawn up by the institution holding the authority and must be obeyed by the publisher of digital Quran.